2016
DOI: 10.1088/1674-1056/25/5/053202
|View full text |Cite
|
Sign up to set email alerts
|

Carrier envelope phase effect on the spatial distribution of high-order harmonic generation in asymmetric molecule

Abstract: The spatial distribution in high-order harmonic generation (HHG) from the asymmetric diatomic molecule HeH 2+ is investigated by numerically solving the non-Born-Oppenheimer time-dependent Schrödinger equation (TDSE). The spatial distribution of the HHG spectra shows that there is little contribution in HHG around the geometric center of two nuclei (z = 1.17 a.u.) and the equilibrium internuclear position of the H nucleus (z = 3.11 a.u.). We demonstrate the carrier envelope phase (CEP) effect on the spatial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[7]. To investigate the effect of two atomic centers, the time-dependent dipole acceleration is divided into two parts as follows: [32] a(t) = a z<0 (t) + a z>0 (t).…”
Section: Resultsmentioning
confidence: 99%
“…[7]. To investigate the effect of two atomic centers, the time-dependent dipole acceleration is divided into two parts as follows: [32] a(t) = a z<0 (t) + a z>0 (t).…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] It can be used to probe the internuclear distance of the diatomic molecule [25][26][27][28] and judge the sign of the dipole phase in the molecular orbital tomography procedure. [12] For asym-metric diatomic molecules, such as HeH 2+ , [29][30][31][32][33][34][35][36][37][38] CO, [39][40][41][42][43] and NO, [44] due to symmetry breaking, both odd and even harmonics are emitted. It has been shown that these odd and even harmonics possess different spectral properties [45][46][47][48] and carry different information of the target, [31,[49][50][51] and therefore need to be studied separately.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Lambert et al [13] discussed the spatial properties of harmonic generation in low order and Zhang et al gave the spatial distribution in HHG from a H + 2 and from a HeH 2+ . [14,15] However, there is no discussion on how to restrain the spatial distribution as far as we know.…”
Section: Introductionmentioning
confidence: 99%